KNOWLEDGE AND AWARENESS LEVELS OF RADIATION RISK FROM MEDICAL IMAGING AMONG SAUDI POPULATION. (CAHIERS MAGELLANES-NS, 2024)
Introduction: Medical radiation imaging techniques enhance surgical outcomes and reduce patient morbidity. The International Commission on Radiation Protection emphasizes maintaining low feasible radiation exposure levels. Studies conducted in Saudi Arabia have revealed gaps in patient and physician awareness regarding radiation risks during medical imaging procedures. This study was conducted to assess knowledge and awareness levels of radiation risk from medical imaging among Saudi population.Methodology: This cross-sectional study was conducted from July to November 2024 in KSA. The study intends to recruit participants via social media sites like Twitter, Snapchat, Instagram, and WhatsApp. The inclusion criteria are Saudi citizens, both males and females, from all provinces of Saudi Arabia, who agree to participate and complete questionnaires. Non-Saudi people and individuals under 18 years old are excluded. The minimum target sample size of 384 was calculated using a Rasosoft calculator, which had a 95% confidence level and a 5% margin of error.Results: The study surveyed 726 participants to assess knowledge and awareness of radiation risks associated with medical imaging in the Saudi population. Findings revealed that 60.9% of respondents felt their physicians did not explain radiation risks, contributing to anxiety observed in 56.9% of participants. The majority (82.5%) reported awareness of these risks, primarily from the internet (51.9%). Despite perceived dangers, 50.4% exhibited low knowledge about radiation risks, with only 21.5% demonstrating substantial understanding. Significant correlations surfaced between knowledge levels and educational background (P=0.028) and occupational status (P=0.004), underscoring a crucial need for enhanced public health education, especially targeting younger demographics.Conclusion: These findings underscore a critical need for enhanced educational initiatives aimed at improving knowledge and awareness of radiation risks associated with medical imaging among the Saudi population.